How can physicists study photosynthesis? History and applications of the photoacoustic technique - Barja , Paulo (Physicae, 2000)
This short review presents the photoacoustic technique applied to the study of photosynthesis. It is known that plants kept in the dark for several hours stop photosynthetic activity. After this dark-adaptation, light incidence gives rise to the socalled photosynthetic induction (restart of the photosynthetic processes). The Open Photoacoustic Cell described here has been used at the Laboratory of Photothermal Spectroscopy (IFGW, UNICAMP) to investigate the kinetics of the photosynthetic induction. Recent work developed at this laboratory includes in vivo and in situ measurements in eucalyptus leaves from different species and subjected to different conditions. With the photoacoustic technique, we can analyze the parameters that influence photosynthesis, such as temperature and intensity of the incident radiation.